The Knowledge of Literature and Literary Studies (KULT_online, 2010)
This monograph dealing with the intricate relationship of literature and knowledge sets out to close a research gap: it is the first book-length study in German that provides a survey of the approaches to this field in literary and cultural studies. Correspondingly, the result is rather complex and voluminous. Over more than 400 pages Klausnitzer outlines the multidimensional relations between literature and knowledge, which are roughly subdivided into four aspects: the inclusion of (specialised) knowledge in literature, the interconnection of literature and cultures of knowledge, the rhetorical and poetic constitution of non-literary knowledge, and the role of literature in historically specific cultures of knowledge.